ATTITUDE OF SELF-HELP GROUP MEMBERS AND NON-MEMBERS OF THRISSUR DISTRICT TOWARDS PANCHAYATI RAJ -A COMPARATIVE STUDY - Anu George; P.J. Rajkamal and R.S. Jiji (Journal of Veterinary and Animal Science, 2012)
A twenty point psychological scale designed following the Likert’s method of summated rating was adopted to compare the attitude of Self-Help Group (SHG) members and non-members towards Panchayati Raj. The scale was administered to a sample, each of 100 SHG members and non-members. The study revealed that just more than half of the SHG members held a favourable attitude towards Panchayati Raj whereas, more than half of the non-members were holding an unfavourable attitude.